Rapid expansion of overseas banking - Eckard Paul Imhof (Intereconomics, 1974)
Since the mid-sixties the expansion of the overseas banking system of American banks accelerated. New impulses will be generated by the “petroldollars” of the oil producing countries which will most likely be handled by the overseas branches.
Keywords: 330; USA